Bactericidal properties of chloramines in relation to mycobacteria - Палій, А. П. (Scientific Progress & Innovations, 2013)
At carrying out researches it is established that disinfectants «Cloramine B» and «Cloramine T» show bactericidal properties of rather atypical mycobacterium and the causative agent of tuberculosis. It is established that «Cloramine B» causes death of mycobacterium at application in concentration of 5,0 % at an exposition 24 hours, and a preparation «Cloramine T» destroys test cultures of mycobacterium at action in concentration of 3,0 % at an exposition 24 hours. It is possible to apply chloramines as reference disinfectant preparations when studying tuberculocidal properties of new chlorine containing disinfectant preparations.